A Study of Selective Motor Fitness Components Empowers On Playing Ability among Low and High Performers of State Level Football Players - Chandrasekaran, S; Anbanandan, A; Krishnaswamy, Suthakar; Balakrishnan, Annida (International Multidisciplinary Research Journal, 2012)
Motor fitness is a present aptitude for physical skills, includes strength and co-ordination enriches today’s Manpower in players performance. The study focuses on selected motor fitness components to ensure the playing ability among low and high performers of State level Football players. To achieve this study, One hundred and fifty men Football players were randomly selected as subjects from Tamilnadu State level men Football Tournament held at Chennai in 2008-09. Their age ranged from20 to 25 years. Selected subjects were classified into three equal groups of each fifty members. Group 1 served as -Chennai Team, Group-II as Salem and Coimbatore Team and Group III Trichy and Madurai Team. All the subjects were oriented the purpose of the test and procedure of conducting this test. Regular activities and training were given that aplomb the player’s ability to perform the game. Questionnaire preparation was also done by our Research Scholar with the reference to the review of the literature. The investigator has provided onto the following selected motor fitness variables such as Cardio-vascular Endurance, Speed, Agility and Explosive Power. The data is collected with the help of five PhD Scholars, Department of Physical Education who were well versed with the conduct of test and collections under the direct supervision of our Research Scholar. Resulting data will be collected before and after the competition and statistically analyzed using ANOVA and DMRT. Hence the study concluded that playing ability solely depends on the physical fitness, stress free mind more than that it relates the socio-economic status to perform the better strategy of playing games.